PERAN PENDIDIKAN KARAKTER DALAM MENGATASI PERUNDUNGAN DI SEKOLAH - Miftahul Mujahidin; Reynar Andaru Ahnaf; Zaki Amrullah Zain; Ismail Ismail; Alfiansyah Habib Arrokhim (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Bullying in school environments has evolved into a multifaceted issue that reflects the growing complexity of student social interactions, particularly alongside rapid digital technology development. It is no longer limited to physical or verbal aggression, but also extends to social exclusion and cyberbullying that occurs through online platforms. Existing responses that rely heavily on punitive measures tend to address surface-level behavior without fully resolving the underlying causes. In response to this limitation, a literature-based inquiry was conducted to reinterpret the role of character education as a preventive framework grounded in value formation. The study draws upon 15 relevant scholarly sources, which were examined comparatively to identify recurring patterns related to forms of bullying, its impacts, and preventive efforts in school contexts. The synthesis of findings indicates that bullying generates consequences that extend beyond victims, affecting perpetrators and bystanders as well, while also shaping the overall school climate. Rather than being an isolated behavioral issue, it emerges as a social phenomenon embedded within the school ecosystem. Strengthening character values such as empathy, responsibility, discipline, respect, and honesty is consistently highlighted as a strategic pathway for prevention. These values are reinforced through classroom learning, school culture, family involvement, and continuous digital literacy development. Overall, the findings emphasize that effective prevention requires a holistic and integrated approach across educational environments rather than fragmented or incidental interventions. ABSTRAK Fenomena perundungan di lingkungan sekolah terus menunjukkan kompleksitas yang tidak sederhana, terutama ketika interaksi sosial peserta didik berkembang seiring penetrasi teknologi digital. Ragam bentuknya tidak lagi terbatas pada kekerasan fisik dan verbal, tetapi juga meluas ke ranah sosial serta cyberbullying yang berlangsung melalui media daring. Dalam berbagai kajian, pendekatan yang menitikberatkan pada hukuman belum sepenuhnya mampu menyentuh akar persoalan perilaku tersebut. Berangkat dari kondisi ini, telaah literatur dilakukan untuk membaca ulang peran pendidikan karakter sebagai strategi pencegahan yang lebih berorientasi pada pembentukan nilai. Kajian ini memanfaatkan 15 sumber relevan yang dianalisis secara komparatif untuk melihat pola temuan terkait bentuk, dampak, dan upaya penanganan perundungan di sekolah. Hasil sintesis menunjukkan bahwa perundungan memberikan konsekuensi tidak hanya bagi korban, tetapi juga pelaku dan saksi, serta berimplikasi pada iklim sosial sekolah secara keseluruhan. Penguatan nilai empati, tanggung jawab, disiplin, hormat, dan kejujuran melalui pembelajaran, budaya sekolah, keterlibatan keluarga, serta literasi digital dipandang berperan penting dalam membangun ekosistem sekolah yang lebih protektif terhadap perilaku perundungan. Temuan ini menegaskan bahwa pencegahan perundungan menuntut pendekatan holistik yang terintegrasi dalam seluruh ekosistem pendidikan, bukan sekadar intervensi insidental di sekolah.